Investigation and evaluation of carbon dioxide emissions from soil in Neris Regional Park - Baltrėnas, Pranas; Pranskevičius, Mantas; Lietuvninkas, Arvydas (Journal of Environmental Engineering and Landscape Management, 2011)
Soils release around 20% of the total CO2 content to the atmosphere; consequently, forest and agricultural ecosystems have a big influence on CO2 balance. Until recently, the majority of CO2 measurements of Lithuanian soils were either carried out under laboratory conditions or obtained by applying outdated research methods. CO2 investigations in Neris Regional Park were carried out under field conditions during plant vegetation by using the CO2 emission measuring instrument ADC BioScientific and soil chamber, the analysis system of which includes a metal collar of ∼0.9 m2 area. This infrared gas analysis system performs measurements within the range of 0–2000 ppm, with an error of 1 ppm. The emission’s error is a mere ±2%. The system allows making reliable measurements within the temperature range of −5 °C to +50 °C. Article in English. Anglies dvideginio emisijų iš dirvožemio neries regioniniame parke tyrimai ir vertinimas Santrauka. Apie 20% viso CO2 kiekio, patenkančio įatmosferą, išskiria dirvožemiai, todėl miškų bei agroekosistemos daro nemažįtaką CO2 balansui. Lietuvoje iki pastarųjų metų dirvožemio CO2 matavimai daugeliu atveju buvo atliekami laboratorinėmis sa˛lygomis, arba duomenys surinkti taikant senstelėjusius tyrimų metodus. CO2tyrimai Neries regioniniame parke atlikti lauko sąlygomis augalų vegetacijos metu matuojant ADC BioScientific CO2 emisijos matuokliu. Šios infraraudonųjų spindulių dujų analizavimo sistemos skalė 0–2000 ppm, paklaida 1 ppm. Emisijos paklaida tesudaro ±2%. Matavimai šiuo prietaisu patikimi −5–+50 °C temperatūroje. Reikšminiai žodžiai: dirvožemis, bendroji anglis, dirvožemio tyrimai, anglies dioksido emisijos. Исследование и оценка выбросов двуокиси углерода из почвы в региональном парке «Нерис» Резюме. Около 20% CO2 от общего объема попадает в атмосферу из почвы, поэтому столь велико влияние лесов и агроэкосистем на баланс CO2. В Литве измерения эмиссий CO2 с поверхности почв проводились в лабораторных условиях либо применялись старые методы исследования. В региональном парке «Нерис» эмиссии CO2 с поверхности почв измерялись новым прибором ADC BioScientific. Для исследований применялся прибор с системой инфракрасного газового анализа по шкале от 0 до 2000 частей на миллион. Выбросы учитывались с погрешностью ±2%. Устройство позволяет надежно измерять эмиссии CO2 в диапазоне температур от −5 °C до +50 °C. Ключевые слова: почва, общее количество углерода, исследования почвы, выбросы двуокиси углерода.